OED Review of the Poverty Reduction Strategy Process : Albania Case Study - Operations Evaluation Department (World Bank, Washington, DC, 2014)
This report analyzes the experience of Albania with the Poverty Reduction Strategy Paper (PRSP) process. The focus of the report is on evaluating the performance of the World Bank in supporting the PRSP initiative, not on appraising the authorities policies. The main emphasis of the report is on the formulation and implementation of the PRSP until March 2003, but it does cover elements of the PRSP Progress Report which was completed following the evaluation team s mission to Albania. The report is structured as follows: Section B describes the country context including, political and economic background, the poverty profile, and key constraints for development. Section C addresses the PRS Process in its entirety and includes an assessment of the relevance of the PRSP for Albania and its consistency with the underlying principles of the initiative. Section D assesses the World Bank s support to the process. Finally, section E summarizes the main points of the assessment and attempts to draw lessons of more general applicability.